2021
DOI: 10.2807/1560-7917.es.2021.26.7.2100065
|View full text |Cite
|
Sign up to set email alerts
|

Reducing contacts to stop SARS-CoV-2 transmission during the second pandemic wave in Brussels, Belgium, August to November 2020

Abstract: To evaluate the effect of physical distancing and school reopening in Brussels between August and November 2020, we monitored changes in the number of reported contacts per SARS-CoV-2 case and associated SARS-CoV-2 transmission. The second COVID-19 pandemic wave in Brussels was the result of increased social contact across all ages following school reopening. Physical distancing measures including closure of bars and restaurants, and limiting close contacts, while primary and secondary schools remained open, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…At baseline, contact with suspected or confirmed cases, especially at home, was positively associated with SARS-CoV-2 infection, as observed in a study that found that physical distancing measures, including limited close contacts while school remained open, controlled SARS-CoV-2 transmission [ 40 ]. However, school contacts had a negative association with this outcome, showing how well-implemented sanitary protocols make the safe opening of schools possible, consistent with other studies that found an association between low transmission and, sanitary recommendations and preventive measures [ 6 , 41 ].…”
Section: Discussionmentioning
confidence: 93%
“…At baseline, contact with suspected or confirmed cases, especially at home, was positively associated with SARS-CoV-2 infection, as observed in a study that found that physical distancing measures, including limited close contacts while school remained open, controlled SARS-CoV-2 transmission [ 40 ]. However, school contacts had a negative association with this outcome, showing how well-implemented sanitary protocols make the safe opening of schools possible, consistent with other studies that found an association between low transmission and, sanitary recommendations and preventive measures [ 6 , 41 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our results agree with the study of Ingelbeen et al . who showed that the proportion of cases among 10–19-year-olds in Brussels did not significantly change after school reopening [ 34 ]. If children were equally susceptible, one might expect even higher ratios of carriership, since they were less restricted in the number of contacts (i.e., due to attendance of summer camps, and given that schools were open as of 1 September 2020 onward).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated 2 sets of ordinary least square (OLS) regressions for each city using a 10- or 20-day delay since COVID-19 incidence changes from school-related NPIs take effect 10 [27] or more days [17, 28, 29] after closures or reopening. Daily new COVID-19 cases were taken for equally spaced time frames with 10- and 20-day delay after the actual school closures and reopening dates.…”
Section: Methodsmentioning
confidence: 99%